- -: FENOMENA GAYA PACARAN ANAK SEKOLAH DASAR DI SD NEGERI 26 PEMECUTAN (Perspektif Pendidikan Agama Hindu) - Mariantika, Ni Putu; Perbowosari, Heny; Muliani, Ni Made (UHN IGB Sugriwa Denpasar, 2024)
The development of globalization and technology has brought significant changes to all aspects of human life, including influencing children's behavior. Nowadays, elementary school children are familiar with dating and are even able to express their feelings to the opposite sex. This phenomenon is important to research so that children are able to understand that elementary school is a time to learn to be a brahmacari. The problem formulation is: (1) The dating style of elementary school children at SD Negeri 26 Pemecutan (Hindu Religious Education Perspective); (2) The impact of the dating style of elementary school children on the learning motivation of students at SD Negeri 26 Pemecutan (Hindu Religious Education Perspective); (3) The role of Hindu Religion and Character education teachers in responding to the phenomenon of elementary school children's dating styles at SD Negeri 26 Pemecutan (Hindu Religious Education Perspective). The purpose of this research is to determine children's dating styles, the impact they have, and the role of Hindu Religious Education and Character teachers in responding to the phenomenon of elementary school children's dating styles at SD Negeri 26 Pemecutan (Hindu Religious Education Perspective). The theory used in this research uses stimulus-response theory and moral foundation theory. Data collection methods use observation, interviews, literature study and documentation, with qualitative descriptive analysis. The research results show:(1) Children in the Hindu perspective are categorized as students (brahmacari), so they are not suitable for dating. The current style of dating for children is done by meeting in person at school/outside of school, and using social media; (2) The impacts that arise are negative and positive impacts; (3) The role of Hindu Religious Education and Character Education teachers is as supervisor, guide and director in educating children based on Hindu religious teachings.